Organometallic reagent-mediated functionalization of aromatic compounds in continuous-flow system - Vasanth, Selvam; Navyatha, Jenu; Senthilkumar, Thanigaivel; Sowntharya, Palanisamy; Dhayalan, Vasudevan (Chemical Engineering & Technology, 2026)
This review describes recent developments in the functionalization of aromatic and heteroaromatic scaffolds using a variety of accessible, reactive organometallic reagents (Li, Mg, Zn, Na, K, etc.) in a continuous-flow process. Many research groups notably demonstrated efficient large-scale conditions for the synthesis of highly functionalized arenes and heteroarenes in moderate to high yields. Flow reactions emphasize reaction scope, tolerance to a wide range of functional groups, clean reactions, commercial availability of starting materials, and high regio- and chemoselectivity. This process will support the sustainable development of biologically important heterocyclic compounds, as well as drugs and natural products. This article reviews work published between 2010 and 2025 and provides a detailed overview, with many applications in organic synthesis and medicinal chemistry.